Risks and resilience of students with hearing impairment in an inclusive school at Bengkala, Bali, Indonesia - Suranata, Kadek; Atmoko, Adi; Bolo Rangka, Itsar; Ifdil, Ifdil (Special Education, 2017)
This phenomenological study describs some risks and sources of resilience of students with hearing impairment in an inclusive school at Bengkala, Bali, Indonesia. The data were obtained from four students with hearing impairment, and some related key informants, through semi-structured in-depth interview and observation. The steps of analyses followed a phenomenological research approach. The result of the study shows that (1) there are three serious risk factors, namely family poverty, student’s difficulties in understanding verbal language and learning materials, and student’s emotional distortion; (2) there are five personal sources of resilience, they involve self-efficacy, cooperation skills, talents or special skills, gratitude, and positive hope; (3) there are four social support sources of resilience, they are family, school, peers, and community. This study also discussed an attempt to improve the success of children with hearing loss through developing psychological and social functioning, and enhancing achievement in inclusive schools.